Factors That Predict Failure in Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction. (June 2017) - Parkinson, Ben; Robb, Curtis; Thomas, Michael; Thompson, Peter; Spalding, Tim
Background: Anatomic graft placement in anterior cruciate ligament (ACL) reconstruction has become the preferred technique for many surgeons. The predictive factors for graft failure in anatomic single-bundle ACL reconstruction are relatively unknown. Purpose: To determine the risk factors for graft failure and the relative importance of those factors in anatomic single-bundle ACL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: All primary anatomic ACL reconstructions undertaken at a single institution over a 2-year period were evaluated for subjective and objective measures of graft failure. Risk factors evaluated included time since ACL rupture, age, sex, body mass index, intact or deficient medial and lateral meniscus, meniscal repair, hamstring graft size, and femoral and tibial tunnel position as assessed by 3D computed tomography (CT) scan. The significant factors predicting failure and the relative importance of those factors were determined. Results: At a median follow-up of 26 months, 123 patients were available for analysis. Ninety-seven patients underwent postoperative 3D CT for tunnel positions, including all 20 cases with graft failure. The significant predictors of graft failure were medial meniscal deficiency (hazard ratio [HR] 15.1; 95% CI, 4.7-48.5; P < .001), lateral meniscal deficiency (HR 9.9; 95% CI, 3-33; P < .001), shallow nonanatomic femoral tunnel positioning (HR 4.3; 95% CI, 1.6-11.6; P = .004), and younger patient age (HR 0.9; 95% CI, 0.9-1; P = .008). Conclusion: Meniscal deficiency is the most significant factor to predict graft failure in single-bundle anatomic ACL reconstruction. Shallow nonanatomic femoral tunnel positioning and younger patient age are additional risk factors for failure, but their relative importance is less.